The breeding and foraging ecology of the House Sparrow in rural and urban environments - Havlíček, Jan (Jihočeská univerzita, 2021)
This study describes the effect of farming practices, farmland utilization, and habitat composition in farmland settlements on the distribution and population density of the House Sparrow. Another goal of this study was to describe food availability for offspring and habitat use in rural and urban settlements. The results imply the importance of farms, their surroundings, small-scale farming, and the presence of natural habitats (shrubs, trees, ruderal vegetation) for the local House Sparrow populations. Increased home range size and flight distance were found in urban breeding pairs, implying the absence or lower availability of critical food sources in the urban environment. Future perspectives, threats, and management recommendations to prevent negative factors affecting House Sparrows and the entire bird community inhabiting similar habitats are discussed in this study.
The breeding and foraging ecology of the House Sparrow in rural and urban environments